The Process of Implementing Extracurricular Badminton in the Institute of Technical Education (ITE) Collage East Singapore 2018 (Universitas Negeri Semarang, 2020)
The purpose of this study was to describe the implementation of extracurricular sports in the badminton at ITE College East Singapore. This research is a descriptive qualitative study conducted at ITE College East Singapore. The time for implementation is in October the fourth week, 2018. The objectives of this study are ITE College East Singapore and badminton extracurricular trainers at ITE College East Singapore. The resource persons of this research are the badminton extracurricular trainers, students and the chair of the sports extracurricular field. Data collection techniques namely observation, interviews, and documentation. As a result of the research, the recuitment process carried out by holding an exhibition was at the beginning of the new school year. The process of implementing activities does not have an exercise program, the schedule is regularly arranged and there is no sparring. There is no goal that belongs to this extracurricular, students only come later practice and go home. Providers of facilities and infrastructure provided are very adequate and of international standard. The conclusion obtained is that badminton extracurricular activities at ITE become a very useful activity because the complete infrastructure provided will encourage students to participate in activities and become better guidelines for the development of sports extracurricular activities at ITE College East Singapore.